Study on Pulse Characteristic of Produced Crude Composition in CO2 Flooding Pilot Test. (13th March 2018) - Diwu, Pengxiang; Liu, Tongjing; You, Zhenjiang; Hou, Ganggang; Qiao, Runwei; Zhao, Lekun
Abstract : It has been observed in many laboratory tests that the carbon number of the maximum concentration components (CNMCC) of produced oil varies monotonically with CO2 injection volume at the core scale. However, in CO2 flooding pilot test at the field scale, we find that the CNMCC is usually nonmonotonic function of CO2 injection volume, which is called "pulse characteristic" of CNMCC. To investigate the mechanism of this phenomenon, we analyze the physical process of CO2 flooding in heterogeneous reservoir and explain the reason of the pulse characteristic of CNMCC. Moreover, two 3D reservoir models with 35 nonaqueous components are proposed for numerical simulation to validate the conjecture. The simulation results show that pulse characteristic of CNMCC only occurs in the heterogeneous model, confirming that the pulse characteristic results from the channeling path between wells, which yields nonmonotonic variation of oil-CO2 mixing degree. Based on it, a new method can be developed to identify and quantify the reservoir heterogeneity.